Quality analysis of Idesia polycarpa fruit oil samples from cultivars with different phenotypes - Tianting Luo; Jiaqi Xu; Zhouqin Zhen; Xue Pan; Lang Feng; Likang Qin; Tingyuan Ren (Food Chemistry: X)
To study the quality characteristics of Idesia polycarpa fruit oil (IPFO) samples under varying phenotypic traits and their differences, three typical phenotypic fruits of the same cultivar were compared, both morphologically and chemically. The results revealed that the highest water content (51.90 %) occurred in small red fruits (RID-S), and the highest oil content (20.63 %) was obtained in large yellow fruits (YID). A total of 532 aroma compounds were identified via gas chromatography–mass spectrometry (GC–MS), with terpenes as the major contributors. The fatty acid composition was dominated by linoleic acid (LA), palmitic acid and oleic acid, and the LA content was highest in large red fruits (RID-B) (1633.25–1807.21 μg/mL), whereas the palmitic acid and oleic acid contents were highest in YID (863.72–976.70 μg/mL and 505.96–604.04 μg/mL, respectively). The oil quality of I. polycarpa varied according to its phenotypic characteristics, with RID-B identified as an excellent cultivar, followed by YID and RID-S.